Evaluation of Village Fund Utilization for Development in Akuni Village, Tinanggea, South Konawe - Madamang, Irwan; Nawawi, Juanda; Syamsu, Suhardiman; Zaenuddin, Ksatriawan (Jurnal Ilmu Manajemen Profitability, 2025)
Village development plays a crucial role in enhancing community welfare in Indonesia, with the Village Fund serving as a key financial instrument under Law No. 6/2014. This study evaluates the effectiveness of Village Fund utilization in physical development projects in Akuni Village, South Konawe Regency, Southeast Sulawesi Province. Adopting a qualitative case study approach, data were collected through in-depth interviews with village officials and community representatives, as well as document analysis. The evaluation framework is based on six key indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The findings indicate that while physical infrastructure development in Akuni Village has shown significant progress, challenges persist in fund allocation flexibility, budget adequacy, and bureaucratic constraints, leading to delays in some projects. Additionally, limited community participation in decision-making has affected the alignment of development priorities with local needs. To enhance the impact of the Village Fund, this study recommends strengthening transparency, optimizing budget planning, and fostering greater community engagement. These insights provide valuable guidance for policymakers and village administrators in designing more efficient and sustainable rural development strategies.